Encontrando o humano na natureza: experiência estética e humanização de profissionais da saúde no solo sagrado de Guarapiranga - Xavier, Miriam Rodrigues [UNIFESP] (2017)
Although the PNH indicates the insertion of humanistic guidelines in the training of the health professional, its presence in higher education is still very timid. Although essential for good medical practice, for many teachers and students the humanities disciplines are regarded as uninteresting. It is covered superficially and students are unaware of the significant breadth of health practices. For a long time, proximity to the patient was almost imperative for the practice of medicine. With the cultural and social changes that have occurred over time, there has been a transformation in medicine and health practice that has led to the discussion of the need for humanization in health. Humanization seeks in the humanizing actions the recovery, not only of physical health, but mainly of respect, right, generosity, subjective expression and the desires of the people. Humanization in health was founded on respect for human vulnerability and on the belief that the relationship of the professional and patient is always subject to emotions that must be guided by the feeling of commitment and compassion that is indispensable in caring for the other. However, without the ability to feel it is impossible to have the ability to care. Therefore the formation of sensitivity is the most important and fundamental need for the development of humanizing training. The present research submitted and approved to the Research Ethics Committee of the Federal University of São Paulo under No. 48419915.3.0000.5505 and counting on 13 professional health professionals aimed to investigate how the aesthetic and reflective experience of nature, Can contribute to humanization in health. The research was applied in the Sacred Ground of Guarapiranga, a space belonging to the World Messianic Church of Brazil. In order to collect the data, we used techniques from both anthropology, in this case participant observation and Oral History of Life, as well as reports written by participants after the end of each meeting. By combining, participant observation, experience reports and oral history of life, a broader view of the experience was possible The analysis of the data happened in the light of the Immersion / Crystallization proposed by Borkan (1999) and much used in ethnographic researches. Observing the images that emerged from the speeches, one could perceive the characterization of three great themes: the emotion, the impact of the first moment, the first contact with the Sacred Ground; The reflection that this impact causes and that leads to an awakening of themselves and also to a new awareness of the other, and finally, on a third level, the change in the way of seeing the world out there. Through the obtained results we can believe that the aesthetic experience of the nature realized in the Sacred Ground of Guarapiranga is potentially humanizing. It causes a profound and transforming affection, typical of an "enlargement of the sphere of being," makes the participants aware, especially in regard to their own lives, lead to a find or to find, generating according to reports, peace and balance. In this way, being good with oneself (using a collaborator's speech) we transmit the good to our neighbor and it is possible to look and care for other people, which for the health area is fundamental. As a product of this research we have developed and presented a Laboratory of Humanities based on the Aesthetic Experience of Nature.